Math question

Math question

Tutors, please sign in to answer this question.

X^2 - 6X -7 =

factor it into ( x - a) ( X-b) , in such a way that

a+ b = 6

ab = -7

a = 7 b= -1

( x -7 ) ( X +1)

1) think of the last number as the PRODUCT of the polynomial. Think of the factors that go into it (when there is no number in front of the x^2, ie the letter (a) in front of the x^2 = 1 (ax^2 +bx +c where a, b, and c are numbers). The only factors of 7 are (1 and 7).

2) the rest is figuring out positive/negative of the factors, if the (b) is negative and the (c) is positive, then both of the factors will have negative numbers (remember.

(x+1) (x-7) will equal the FOIL (first, outside, inside, last). - the -7x +1x equals the -6x you need.

The way to solve this is to ask yourself the question:

What two factors have a sum of -6 (the coef of the x term) and a product of -7 (the coef of the constant) ...

After a little thought you will realize that 1 * -7 = -7 and 1 + -7 = -6

... Let me know if you need any more help.